Produção, deformação a frio e recristalização da liga Ti-35Nb-0,15Si - Cabral, Helton José Rodrigues (2013)
This work studied the deformation and recrystallization in Ti-35Nb-0,15Si alloy. Were produced alloys with four different compositions in arc melting furnace under controlled argon atmosphere. The amount of Nb was kept constant at 35 wt% and the amount of Si ranging between 0.15 and 0.55% wt%. The amount of Ti ranging according amount of Si. The alloys were homogenized at 1000 ° C for 8 hours, and then cold-deformed by compression in a matrix. Deformed alloys were recrystallized at the temperatures of 500, 600 and 700 ° C for 1 hour in the differential thermal analysis equipment (DTA). Were used techniques of the optical microscopy, X-ray diffraction and microhardness to evaluate the changes caused by the deformation and the recrystallization. The alloy with the composition Ti-35Nb-0, 15Si showed the highest level of deformation, resulting in increased hardness and formation of a martensitic phase. DTA curves provide information about the ß transus temperature, recovery and recrystallization of the alloys. The recrystallization at 500, 600 and 700 ° C propitiated stress relief, decreasing in the amount of a" and hardness reduction.